A influência da religião na formação dos hábitos alimentares: estudo do adventismo do sétimo dia - Campelo, Karla Josnaina Soares (2015)
This research analyzes the influence of religion in the formation of eating habits. For this purpose, we focus attention on the eating habits of Seventh-day Adventists. Seventh-day Adventist Church preaches healthy eating habits, considering them an important requirement for maintaining the body - the temple of God - in a state of purity. The concern with healthy eating is related to a religious obligation held by the faithful. Initially, we present a historical overview of the Seventh-day Adventist Church, focusing on the life and teaching of William Miller and Ellen G. White. We then present the relationship between religion and eating, highlighting the diet proposed by Ellen G. White and the Seventh-day Adventist Church. Finally, we verify the food proposal of Adventists from the scientific literature in the field of nutrition.